Respuestas
Respuesta dada por:
1
2x - 3= 3/2 - 1/9
2x(18) -3 (18) = 3/2 (18) - 1/9 (18) (m.c.m)
36x-54=27-2
36x=79
x=![\frac{79}{36} \frac{79}{36}](https://tex.z-dn.net/?f=+%5Cfrac%7B79%7D%7B36%7D+)
Espero que sirva! Saludos!
2x(18) -3 (18) = 3/2 (18) - 1/9 (18) (m.c.m)
36x-54=27-2
36x=79
x=
Espero que sirva! Saludos!
Respuesta dada por:
1
2x-3=
-![\frac{1}{9} \frac{1}{9}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B9%7D+)
18(2x-3)=3-1
36x=2+54
18(2x-3)=3-1
36x=2+54
lila36605:
espero que te ayude !!!
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años